2014
DOI: 10.1128/jvi.01046-14
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Antiretroviral Treatment Initiated at Primary HIV-1 Infection Affects the Size, Composition, and Decay Kinetics of the Reservoir of HIV-1-Infected CD4 T Cells

Abstract: Initiation of antiretroviral therapy during the earliest stages of HIV-1 infection may limit the seeding of a long-lasting viral reservoir, but long-term effects of early antiretroviral treatment initiation remain unknown. Here, we analyzed immunological and virological characteristics of nine patients who started antiretroviral therapy at primary HIV-1 infection and remained on suppressive treatment for >10 years; patients with similar treatment duration but initiation of suppressive therapy during chronic HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
190
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(226 citation statements)
references
References 44 publications
32
190
1
3
Order By: Relevance
“…Recent reports in both adults and children have indicated that early and sustained full suppression of HIV may limit viral reservoirs 58, 59 and that a longer cumulative time spent with ongoing viral replication is associated with a larger viral reservoir 60. How this may relate to future ‘cure’ is yet to be determined, but it should also be borne in mind when considering ART initiation in young children who may see the advent of new curative treatments within their lifetime.…”
Section: When To Start Artmentioning
confidence: 99%
“…Recent reports in both adults and children have indicated that early and sustained full suppression of HIV may limit viral reservoirs 58, 59 and that a longer cumulative time spent with ongoing viral replication is associated with a larger viral reservoir 60. How this may relate to future ‘cure’ is yet to be determined, but it should also be borne in mind when considering ART initiation in young children who may see the advent of new curative treatments within their lifetime.…”
Section: When To Start Artmentioning
confidence: 99%
“…2 Furthermore, HIV replication, diversity, persistence in tissue compartments and reservoirs complicate clinical outcomes and pose a threat to therapeutic management and cure strategies. 3,4 HIV-1 diversity is a function of its error-prone reverse transcriptase, replication rate, recombination, and host selective pressures. 5 Following transmission, HIV-1 spreads to various anatomical sites where the site-specific microenvironment regulates its evolutionary kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Buzon, et al showed a correlation between the frequency of cells with replication-competent HIV-1, and the total amount of HIV-1 DNA in suppressed patients with treatment initiated at different phase of the infection. However, in this study, residual viremia did not seem to be dependent on the levels of HIV-1 DNA [39].…”
Section: Panelmentioning
confidence: 74%